TINJAUAN KHUSUS KOLEKSI TUMBUHAN BERUSIA TUA DI KEBUN RAYA CIBODAS - Muhamad Muhaimin; Muhammad Efendi (Bioma, 2018)
ABSTRACT Cibodas Botanical Garden (CBG) is one of the oldest institutions in Indonesia to concern in ex-situ plant conservation and montane plant research. This institution was established since 1852, initiated by introduction of quinine plant (Cinchona calisaya) for the first time in Indonesia. After that, CBG has brought many species of plants to be conserved and then further studied. As an institution that has been established for more than 166 years, CBG have many plants collection that are old or more than 50 years old. However, a study that discuss about old plants collection from CBG has not been widely carried out, even though the study is very important for manage and develop of plant conservation in CBG. Therefore, this paper aims to provide a review about old plants collection in CBG, ranging from about composition of taxa, distribution of collection, habitat origin, conservation status, management collection, and potential development in the future. The results of this paper are expected to further increase the value of the plant collection in CBG and provide guidance for administrator and all stakeholders to develop various potential found in CBG’s plant collection, especially from old plants collection. Keywords: Cibodas Botanical Garden, management collection, old plants collection, potential plants